2015
DOI: 10.1021/nn506792d
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Thermal Transport in Ultrathin Silicon Membranes by Surface Nanoscale Engineering

Abstract: A detailed understanding of the connections of fabrication and processing to structural and thermal properties of low-dimensional nanostructures is essential to design materials and devices for phononics, nanoscale thermal management, and thermoelectric applications. Silicon provides an ideal platform to study the relations between structure and heat transport since its thermal conductivity can be tuned over 2 orders of magnitude by nanostructuring. Combining realistic atomistic modeling and experiments, we un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
162
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(175 citation statements)
references
References 54 publications
(121 reference statements)
12
162
0
1
Order By: Relevance
“…We observe, expectedly, k Memb to drop significantly with decreasing d due to dispersion modification as well as the reduction of phonon mean free paths (MFP) caused by diffuse boundary scattering at the surfaces as a result of their reconstruction at the equilibrium state [23]. These effects been studied experimentally in the literature in the context of a thin silicon layer on a substrate [24], freestanding silicon membranes [12,25], and also silicon nanowires [26]. The k NPM curves are observed to similarly increase with increasing unit-cell size (due to increasing thickness) until gradual saturation.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…We observe, expectedly, k Memb to drop significantly with decreasing d due to dispersion modification as well as the reduction of phonon mean free paths (MFP) caused by diffuse boundary scattering at the surfaces as a result of their reconstruction at the equilibrium state [23]. These effects been studied experimentally in the literature in the context of a thin silicon layer on a substrate [24], freestanding silicon membranes [12,25], and also silicon nanowires [26]. The k NPM curves are observed to similarly increase with increasing unit-cell size (due to increasing thickness) until gradual saturation.…”
mentioning
confidence: 82%
“…A recent molecular dynamics study examined a wider range of geometric dimensions on the same pillared silicon membrane configuration and demonstrated a reduction in the thermal conductivity by roughly a factor of 3 [11]. The resonance-hybridization mechanism described above may be used in conjunction with boundary scattering from rough surfaces to lower k [12,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Xiong et al [32] demonstrated that nanopillars not only generate local resonances but also scatter the phonons and reduce their mean free path by one order of magnitude. Similarly, Neogi et al [61] concluded that the reduction in thermal conductivity is mainly caused by the diffuse scattering of phonons on nanopillars whereas local resonances play only a minor role. Recently, Honarvar and Hussein [34] too found that nanopillars shorten both phonon mean free path and lifetimes by the diffuse scattering, but argued that local resonances still play the leading role in the thermal conductivity reduction.…”
Section: Simulations Of Heat Conductionmentioning
confidence: 98%
“…Thus, the observed reduction in thermal conductivity was attributed to the surface roughness and the amorphous layer under the pillars. Indeed, amorphous layers at the surfaces are known to reduce the thermal conductivity of nanostructures [61,6466] and can diffusely scatter phonons stronger than just surface roughness [67]. …”
Section: Experimental Measurements Of the Thermal Propertiesmentioning
confidence: 99%